The sociology of Norbert Elias - Loyal, Steven; Quilley, Stephen; Cambridge University Press (Cambridge, UK ; New York : Cambridge University Press, 2004)
"Over recent years there has been a steady upsurge of interest in the work of Norbert Elias. This book provides a comprehensive and accessible introduction to the key aspects of Elias's work and then applies an Eliasian approach to key topics in contemporary sociology such as race, class, gender, religion, epistemology and nationalism. The editors have brought together a distinguished group of international sociologists and this book will not only change the course of Elias studies but be a valuable resource for both students and scholars alike."-- Publisher's description
Towards a 'central theory': the scope and relevance of Norbert Elias / Stephen Quilley and Steven Loyal -- Sociology as a Human Science: Norbert Elias and the Sociology of Knowledge: -- From distance to detachment: knowledge and self-knowledge in Elias's theory of involvement and detachment / Richard Kilminster -- Ecology, 'human nature' and civilising processes: biology and sociology in the work of Norbert Elias / Stephen Quilley -- Between the real and the reified: Elias on time / Barry Barnes -- Processes of Stratification: Figurations of Race, Class and Gender: -- The figurational dynamics of racial stratification: a conceptual discussion and developmental analysis of black-white relations in the United States / Eric Dunning -- Decivilising and demonising: the social and symbolic remaking of the black ghetto and Elias in the dark ghetto / Loi;c Wacquant -- Elias on class and stratification / Steven Loyal -- Elias on gender relations: the changing balance of power between the sexes / Christien Brinkgreve -- The Formation of Individuals and States: -- Not so exceptional? State-formation processes in America / Stephen Mennell -- Armed peace: on the pacifying condition for the co-operative of States / Paul Kapteyn -- Changing regimes of manners and emotions: from disciplining to informalizing / Cas Wouters -- Elias and modern penal development / John Pratt -- Elias, Freud and Goffman: shame as the master emotion / Thomas Scheff -- Religion and Civilising Processes: Weber and Elias Compared: -- Weber and Elias on religion and violence: warrior charisma and the civilising process / Bryan Turner -- Christian religion and the European civilising process: the views of Norbert Elias and Max Weber compared / Johan Goudsblom
Includes bibliographical references and index
Keywords: Elias, Norbert, -- 1897-1990.; Historical sociology; Civilization, Modern; Social structure; Self-consciousness